Reconstruction of the Principle of People’s Sovereignty Based on the Perspective of Fiqh Siyasah - Rahmad Lubis; Riswan Hadi Lubis; Heri Sulaiman; Desi Purnama; Nuranisah Nuranisah; Nur Isyanto (KARSA Journal of Social and Islamic Culture, 2025)
The principle of popular sovereignty constitutes a fundamental doctrine in modern constitutional democracy, positioning the people as the ultimate source of political legitimacy. However, within Islamic political thought, this principle has often been perceived as theoretically problematic due to its assumed tension with the doctrine of divine sovereignty (ḥākimiyyah Allāh). This article aims to reconstruct the principle of popular sovereignty from the perspective of fiqh siyasah, moving beyond the conventional dichotomy between divine sovereignty and popular authority. Employing a normative-philosophical approach combined with conceptual and historical analysis, this study examines classical Islamic political doctrines alongside contemporary theories of sovereignty and constitutionalism. The findings demonstrate that fiqh siyasah does not reject popular sovereignty per se, but rather reframes it as a form of delegated, ethically bounded authority. Sovereignty, in this perspective, is not an absolute right of the people to legislate without limits, but a collective mandate exercised within the normative framework of Islamic law and oriented toward the realization of justice and public welfare (maqāṣid al-sharī’ah). Popular will acquire legitimacy not merely through procedural majority, but through its conformity with substantive ethical principles. This reconstruction offers a conceptual synthesis between Islamic political jurisprudence and modern democratic governance. It further shows that democratic institutions in Muslim-majority states can operate within a framework of constitutional and ethical sovereignty without negating Islamic normative foundations. In the Indonesian context, this model provides a theoretical basis for strengthening substantive democracy by integrating popular sovereignty with constitutional values and moral accountability. The article contributes to contemporary Islamic political thought by offering a prescriptive framework that bridges normative Islamic principles and modern constitutional practice.